WINFOLIA FLAG LEAF ANALYSIS OF WINTER WHEAT (TRITICUM AESTIVUM L.) AND EVALUATION OF GRAIN QUALITY INDICATORS (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2024)
Winter wheat (Triticum aestivum L.) is one of the most widespread and economically beneficial crops in Latvia. Wheat grain yield and quality are strongly related to the growing conditions of crop that are possible to improve agronomically by carrying out an appropriate soil tillage and growing it in a well-planned crop sequence. The aim of the study to determine soil tillage system and precrop influence to winter wheat flag leaf parameters and grain yield quality indicators. A two-factor field trials was set up in the Latvia University of Life Sciences and Technologies training and research farm “Peterlauki” in 2022/2023: 1. soil tillage system and 2. precrop. The basic indicators of flag leaf length, width (cm) and flag leaf area (cm2) of a winter wheat were detected using a scanner STD4800 and the specialized computer program WinFOLIA Regent Instruments Software were determined from 10 plants in each variant. Three samples from each variant were taken for yield determination and structural elements of crops. Winter wheat 1000 grain weight and grain quality indicators were determined in Grain and Seed study and research laboratory of LBTU. Winter wheat precrop did not significantly affect (p>0.05) grain yield in the trial year, but the lowest yield was obtained in the conventional soil tillage system where wheat was grown in repeated sowings (5.1 t ha-1), and the highest yield in the minimal soil tillage system where precrop was field beans (7.0 t ha-1). The larger winter wheat flag leaf area was determined in both soil tillage systems, if the winter wheat precrop was field beans, the relationships are not significant (p>0.05).;